Cameroon : Fourth Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility, and Requests for Extension of Arrangement, Waiver of Performance Criterion, and Extension of Interim Assistance Under the Enhanced Initiative for Heavily Indebted Poor Countries. (IMF Staff Country Reports; Country Report ;, 2003)
Overall, the program's macroeconomic targets have been broadly met. The program embodies a renewed emphasis on the non-oil revenue mobilization effort and continuation of a prudent expenditure stance. Reversing the deterioration of the financial operations of the public companies and the utilities is critical. The key objective is strengthening fiscal transparency. Executive Directors welcome the government's commitment to move forward with the implementation of structural reforms. Close and sustained monitoring, and enhanced coordination within the government, will be critical to the successful implementation of the program.